Community Participation in Local Governments: Public Consulting and Transparency in Gaza Strip, Palestine - Enshassi, Adnan Ali; Kullab, Ahmed S (International Journal of Sustainable Construction Engineering and Technology, 2014)
The objectives of this study are to identify and examine the community participation strategies concerning consultation and information disclosure and to identify and evaluate major barriers to community participation development. A questionnaire survey was developed to elicit the perceptions of the municipality’s officials (top management and/or mayors of the selected sample) of Gaza Strip municipalities regarding community participation practice. The results indicated that there is a weak transparency (information disclosure) and community consultation in the municipalities of Gaza Strip. The findings revealed that, the major barriers of information disclosure approach are due to legal challenges, public awareness, lack of community members’ skills and knowledge and social factors. In addition, the major barriers of community consultation are mainly due to lack of community members’ skills and knowledge, lack of social capital and trust of local people in their leaders, political, economic challenges, community culture and municipality council awareness. It is recommended to expand the scope of public participation and developing strategies that maximize citizen input in community development activities in local governments of Gaza Strip. The findings can assist in identifying new directions for enhancing public participation in Gaza Strip local governments